Pengaruh Unsafe Action, Usia dan Masa Kerja Terhadap Kecelakan Kerja - Syntiya Rachmadani Putri; Winarko Winarko; Suprijandani Suprijandani; Demes Nurmayanti; Marlik Marlik (Jurnal Penelitian Kesehatan SUARA FORIKES, 2024)
The aims of this study were to determine the effects of unsafe actions, age and length of work on work accidents of workers. This is a qualitative research using literature review method. To gather data, Literature search results from previous researchers published from year 2016 to 2021 were used and selected by matching the criteria of topics and research variables. The obtained data will be presented with a table and will be analyzed descriptively. In this study, the results of work accidents occurred in the workplace ranged from 6.3% to 95.5% with the average worker who suffered a work accident of 46.5%. Unsafe actions in the workplace ranged from 8.8% to 97% with an average of 53.8% of unsafe actions. The influence of age unsafe action factors on work accidents shows a percentage of 65% and the influence of time unsafe action factors on work accidents shows a percentage of 75%. The results of the study can be concluded that the factors of unsafe actions, age and length of work affect work accidents. Increased efforts of knowledge and skills by fostering workers so that awareness about occupational health and safety will increase.Keywords: unsafe action; age; working period; work accident